2000
DOI: 10.1104/pp.122.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Plastidic Protoporphyrinogen IX Oxidase Leads to Resistance to the Diphenyl-Ether Herbicide Acifluorfen

Abstract: The use of herbicides to control undesirable vegetation has become a universal practice. For the broad application of herbicides the risk of damage to crop plants has to be limited. We introduced a gene into the genome of tobacco (Nicotiana tabacum) plants encoding the plastid-located protoporphyrinogen oxidase of Arabidopsis, the last enzyme of the common tetrapyrrole biosynthetic pathway, under the control of the cauliflower mosaic virus 35S promoter. The transformants were screened for low protoporphyrin IX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 41 publications
1
78
0
1
Order By: Relevance
“…To measure the Proto IX content, plant tissue (0.1 g) was ground in 1 ml methanol : acetone : 0.1 N NaOH (9 : 10 : 1) and the homogenate was centrifuged at 10,000 g for 10 min to remove cell debris. 19) Proto IX was separated by HPLC as described above.…”
Section: Protoporphyrinogen Oxidase Activity and Protoporphyrin IX Comentioning
confidence: 99%
See 2 more Smart Citations
“…To measure the Proto IX content, plant tissue (0.1 g) was ground in 1 ml methanol : acetone : 0.1 N NaOH (9 : 10 : 1) and the homogenate was centrifuged at 10,000 g for 10 min to remove cell debris. 19) Proto IX was separated by HPLC as described above.…”
Section: Protoporphyrinogen Oxidase Activity and Protoporphyrin IX Comentioning
confidence: 99%
“…Protox activity was determined following the method of Lermontova and Grimm. 19) The Protogen IX substrate was prepared by chemical reduction of Proto IX with sodium mercury amalgam (Sigma-Aldrich, St. Louis, MO, USA). The assay contained 70 ml suspension of crude chloroplasts and mitochondria (0.5 mg protein) and 140 ml assay buffer.…”
Section: Protoporphyrinogen Oxidase Activity and Protoporphyrin IX Comentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has suggested that nuclear gene expression might be controlled by the levels of the chlorophyll precursor protoporphyrin IX (Lermontova and Grimm, 2000). To verify whether the differences in cor14b accumulation among albino and xantha mutants could be correlated with protoporphyrin IX levels, we have determined protoporphyrin IX levels in xantha f17 and xantha-s46 before and after cold stress treatment by using the method of Lermontova and Grimm (2000).…”
Section: Chlorophyll Precursors Levels Are Not Affected By Chloroplasmentioning
confidence: 99%
“…Glyphosate 저항성 콩은 glyphosate 저항성 클론 cp4 EPSPS를 콩에 삽입시켜 개발되었으며, 면화, 옥 수수, 캐놀라, 알팔파, 벤트그라스(Agrostis stolonifera), 사 탕무 등에서도 glyphosate 저항성 형질을 도입한 형질전환 체들이 개발되었다 (Pasgette et al, 1996). 그리고 엽록소 생합성을 저해하는 acifluorfen의 형질전환작물은 엽록소 생합성과 관련된 목표 효소의 과대발현을 통하여 개발되 었다 (Lermontova and Grimm, 2000). 두 번째 시도는 glufosinate와 bromoxynil 저항성으로, 이 들의 제초활성 물질이 작물에서 무독성인 물질로 전환하 는 제초제 대사를 증진하는 유전자의 도입에 의하여 이루 어졌다 (Haumann, 1997).…”
unclassified